PENGARUH PENGEMBANGAN KARIR DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA RUMAH SAKIT IBU DAN ANAK SAMMARIE WIJAYA JAKARTA SELATAN - Dhea Amalia Putri; Andri Priadi (Al Hasanah Barokah Foundation, 2026)
This study aims to analyze the effect of career development and teamwork on employee performance at Sammarie Wijaya Mother and Child Hospital in South Jakarta. Data collection methods include observation, questionnaires, interviews, and literature studies. The approach used is associative quantitative with a questionnaire containing 10 statements each for career development, teamwork, and employee performance. The sample involved 52 employees. The data were analyzed using SPSS version 29, with validity, reliability, classical assumption, coefficient, regression, and hypothesis testing. The results showed the regression model Y = 5.033 + 0.262 X1 + 0.638 X2. The R Square value was 0.769, meaning that career development and teamwork simultaneously affect employee performance by 76.9%, while the remaining 23.1% is influenced by other factors not studied.